Prevalence of depressive symptoms and associated factors among foreign caregivers: A cross‐sectional study - Hsuan‐Cheng Su; Sophia H. Hu; Mei‐Ju Chi; Yen‐Kuang Lin; Chih‐Yu Wang; Trung V. Nguyen; Yeu‐Hui Chuang (Wiley, 2023)
Abstract Aim To understand the prevalence of depressive symptoms among foreign caregivers and the associated factors. Design A cross‐sectional study. Methods Data from 178 Indonesian foreign caregivers, selected based on convenience and snowball sampling in Taiwan, were collected between July 2019 and February 2020 using questionnaires. Stepwise multiple linear regression was used to identify the factors associated with depressive symptoms. Results Approximately 30.3% of the foreign caregivers displayed depressive symptoms. The symptoms were more prevalent among the participants who were younger; had more social support; shared a bed with others; and experienced higher work‐related stress, more loneliness and physical discomfort. The findings suggest that nurses or nurse practitioners visiting patients at home should not only deliver care for them but also show concern for the psychological well‐being of the foreign caregivers of these patients. Moreover, interventions should be developed to alleviate or prevent the emergence of depressive symptoms among foreign caregivers.